2010
DOI: 10.1111/j.1460-9568.2010.07482.x
|View full text |Cite
|
Sign up to set email alerts
|

β-Secretase activity in rat astrocytes: translational block of BACE1 and modulation of BACE2 expression

Abstract: BACE1 and BACE2 are two closely related membrane-bound aspartic proteases. BACE1 is widely recognized as the neuronal β-secretase that cleaves the amyloid-β precursor protein, thus allowing the production of amyloid-β, i.e. the peptide that has been proposed to trigger the neurodegenerative process in Alzheimer's disease. BACE2 has ubiquitous expression and its physiological and pathological role is still unclear. In light of a possible role of glial cells in the accumulation of amyloid-β in brain, we have inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 45 publications
3
25
0
Order By: Relevance
“…Primary rat hippocampal neurons (ϳ80% purity) or pure astrocytes were prepared from 2-to 3-d-old Sprague Dawley rats, in respective accordance with Codazzi et al (2006) and Bettegazzi et al (2011). The Institutional Animal Care and Use Committee of the San Raffaele Scientific Institute approved the experimental procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Primary rat hippocampal neurons (ϳ80% purity) or pure astrocytes were prepared from 2-to 3-d-old Sprague Dawley rats, in respective accordance with Codazzi et al (2006) and Bettegazzi et al (2011). The Institutional Animal Care and Use Committee of the San Raffaele Scientific Institute approved the experimental procedures.…”
Section: Methodsmentioning
confidence: 99%
“…In keeping, recent studies in vitro confirmed that, under normal conditions, astrocytes possess the APP-processing machinery for generating Aβ peptide, i.e., APP itself, BACE1 and/or its close homolog BACE2. 76,80,81 Furthermore, Aβ peptide was described to transcriptionally regulate the expression of the astrocytic BACE1 via the calcineurin/nuclear factor of activated T cells 4 (NFAT4) or nuclear factor-κB (NF-κB) signaling pathways, 82,83 suggesting a feed-forward mechanism to maintain or amplify Aβ deposits in astrocytes. More controversial is the issue of reactive astroglia as some studies indicated that cultured astrocytes, activated with cytokine combinations, positively regulate β-secretase activity and Aβ secretion, 84 whereas others found opposite results.…”
Section: Alzheimer Diseasementioning
confidence: 99%
“…More controversial is the issue of reactive astroglia as some studies indicated that cultured astrocytes, activated with cytokine combinations, positively regulate β-secretase activity and Aβ secretion, 84 whereas others found opposite results. 76 A correlation between the deposition of Aβ protein in the extracellular space of forebrain regions and the progressive decline in cognitive functions was originally established in morphological and biochemical studies in AD patients. [85][86][87] Subsequent results obtained in various transgenic AD models provided additional evidence that cognitive deficits are the consequence of the synaptic failure induced by Aβ.…”
Section: Alzheimer Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The physiological and pathological role of BACE2 remains unclear. BACE2 is expressed in glial cells and may contribute to Aβ generation within this cell type although the mechanism requires elucidation [35, 45]. Glial cells play a role in AD amyloidogenesis, and early evidence for a role for BACE2 in glial amyloidogenic processing in Down syndrome patients suggests further investigation.…”
Section: In Vivo Validation Of Bace1 As the Alzheimer's β-Secretasementioning
confidence: 99%